ANALYSIS OF THE EFFECT OF HUMAN RESOURCE COMPETENCY, USE OF INFORMATION TECHNOLOGY, BUDGETING AND SUPERVISION PARTICIPATION ON ACCOUNTABILITY OF VILLAGE FUNDS MANAGEMENT IN MUSI BANYUASIN INDONESIA REGENCY - Syuroh, Mat (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to analyze the significance of the influence of human resource competencies, utilization of information technology, budgeting participation and supervision of village fund management accountability in Musi Banyuasin Regency. The population and sample in this study were all parties involved in the preparation of the Village Income and Expenditure Budget in the Village Government in the area of Musi Banyuasin Regency as many as 77 people, so this study was a census study. Data collection methods used: Questionnaire and Documentation. Data analysis techniques using validity test, reliability test, classic assumption test, and multiple linear regression analysis, t-test, F-test and coefficient of determination. The results of the study concluded that: There is a significant positive effect on Human Resources Competence in Village Fund Management Accountability. There is a significant positive effect of Information Technology on Village Fund Management Accountability. There is a significant positive effect of Budgeting Participation on Village Fund Management Accountability. There is a significant positive effect of Oversight on Village Fund Management Accountability.